Selective release of excreted DNA sequences from phytohemagglutinin-stimulated human peripheral blood lymphocytes. Effects of trypsin and divalent cations. - Distelhorst, C W (1978)
We studied the synthesis of excreted DNA sequences and their release from phytohemagglutinin-stimulated human peripheral blood lymphocytes under conditions permitting optimal cell growth. Cells were labeled by constant exposure to low specific activity [3H]thymidine. Excreted DNA sequences were synthesized during the period of logarithmic cell growth and moved slowly from the high molecular weight chromosomal DNA fraction into the low molecular weight cell DNA fraction (Hirt supernate) from which they could be specifically released by treating the cells briefly with small amounts of various proteases; 1 microgram/ml trypsin for 5 min was optimal. On day 5 of culture, 13.3 +/- 6.9% of the total cellular acid-precipitable [3H]thymidine was released by this treatment. Trypsin-induced release was partially and reversibly inhibited by incubating the cells for 16 h with 5 mM dibutyryl-cyclic AMP. Cells incubated in the absence of divalent cations spontaneously released this Hirt supernatant DNA; after maximal release had occurred under these circumstances, additional trypsin treatment caused no further release of DNA. Trypsin-induced DNA release could be completely and reversibly inhibited by incubating the cells in the presence of 10 mM calcium. Trypsin-released DNA was isolated and analyzed by reassociation kinetics. A major component, representing 54% of the DNA, reassociated with a C0t1/2 of 68 mol.s/liter (the value at which DNA association is 50% complete). The reassociation of this DNA was studied in the presence of an excess of DNA isolated from stimulated lymphocytes on day 3 in culture, and in the presence of an excess of resting lymphocyte DNA. The high molecular weight fraction of day-3 cell DNA contained three times more copies of the trypsin-released DNA major component as compared to resting lymphocyte DNA. Hirt supernatant DNA isolated from day-5 stimulated lymphocytes reassociated in an intermediate component representing 34% of the DNA with a Cot1/2 of mol.s/liter; after cells were treated with trypsin, this component could no longer be identified in the Hirt supernatant fraction, presumably because it had been released into the incubation medium. These data describe a quantitatively reproducible system with which synthesis and release of excreted DNA sequences can be studied.